ChemInform Abstract: Ceria‐Containing Ordered Mesoporous Silica: Synthesis, Properties, and Applications. Issue 12 (March 2016) - Pal, Nabanita; Cho, Eun‐Bum; Patra, Astam K.; Kim, Dukjoon
Abstract: Review: 132 refs.